Early Detection of Non-Communicable Diseases (NCDs) in the Elderly in the Working Area of the Bongomeme Health Center, Gorontalo Regency - Abdulah A. Nunua; Rosmin Ilham; Hamna Vony Lasanuddin (Universitas Muhammadiyah Palu, 2026)
The elderly are someone who has reached the age of 60 years and above. The elderly group is a vulnerable age group. In this age range, there is a variety of risks of non-communicable diseases (NCDs) caused by degenerative factors such as hypertension, diabetes mellitus, osteoporosis, and cancer. Generally, the increase in the incidence of some of these diseases tends to increase with age, so it is more experienced by the elderly. This study aims to find out the picture of early detection of non-communicable diseases (NCDs) in the elderly in the working area of the Bongomeme Health Center, Gorontalo Regency. The population in this study is all elderly people aged 60 years in the working area of the Bongomeme Health Center, Gorontalo Regency, which amounts to 3200 elderly people. The sampling technique in this study uses the non probability sampling method with the puposive sampling technique, the sampling of this study uses the 10% slovin formula , the sample size is 97 respondents. This research method uses quantitative descriptive research with an analytical descriptive research model with an observational approach. The results showed that the status of NCDs showed that most of the elderly were detected to have Non-Communicable Diseases (NCDs), namely 59 respondents (60.8%), while 38 respondents (39.2%) were not detected to have NCDs. The most common type of NCD found in the elderly is hypertension, followed by diabetes mellitus, heart disease, chronic respiratory disease, and stroke. The conclusion in this study is that most of the elderly in the Bongomeme Health Center area, Gorontalo Regency are detected with NCDs, so it is necessary to strengthen early detection and prevention efforts in a sustainable manner.